The Treaty of Lisbon of 1864: the demarcation of the border and the national identifications - Cairo Carou, Heriberto; Godinho, Paula (Historia y Política, 2016)
he Treaty of Boundaries between Spain and Portugal, signed in Lisbon in 1864, is paradigmatic of the modern treaties of inter-state borders. In this article it is studied first the works of the Mixed Commission of Boundaries created to this object, and its relation with the population of the «line» (raya) –local name for the adjacent zone to the border–, then we analyze the diplomatic negotiations and the final text of the Treaty. The identity discourses on which the demarcation of border is based are specified in order to show its relation with the processes of national identification. It is necessary to differentiate three levels in these discourses: the «palace» discourse of the central authorities and diplomats, the technical and progressive discourse of the military engineers and topographers of the Commission, and, finally, the local people discourse.